Features of reproductive behaviour of students on the example of the Tambov region of the Russian Federation - V. A. Filippenko (Вестник университета)
The article provides an analysis of the demographic situation in the Tambov region and regional policy on this issue. There is a difficult demographic situation in the entity under consideration. Based on the results of the sociological study of the student youth of the region, a high degree of importance of self-realisation, self-development, and achievement of material well-being is revealed. The creation of a family becomes less important in the life goals of the student youth. The dependence of the respondents’ reproductive plans on their idea of what life will be like. The more confident young people are in life success, the more confident they are about having children. A person’s commitment to religion can have a strong impact in the case of unplanned pregnancy and the decision to have an abortion. For a more complete realisation of the possibilities of reproductive behaviour of the young people, it is necessary to develop measures of both regional and federal support, since these measures can have a positive impact on the factor of confidence in the future and also that in the case of a difficult life situation, a young family will always have the opportunity to ask someone for help. In addition, it is especially important to form ideas about the possibility of successfully combining parental responsibilities, self-realisation and career building. For a deeper understanding of these processes, it is necessary to continue studying this issue.